Investigation of combined effects of wax, calcites and clay on emulsion stability using response surface methodology - Umar, A.A. (Emerald Group Holdings Ltd., 2019)
Purpose: This paper aims to examine the effect of wax, calcites and clay on the stability of petroleum emulsions. It proposes a proxy model that takes into cognizance the presence of solids other than asphaltene and resin. This study aims to investigate the combined effects of these solids on the stability of emulsions and show their relevance or otherwise in the creation of petroleum emulsions. Design/methodology/approach: This paper used synthetic emulsions based on a response surface methodology using different weight concentrations of wax, calcites and clay. A BoxâBehnken design model was adopted and the effects of the different variables on emulsion stability were analyzed. The conventional visual observation (batch testing) was augmented with a more robust technique of studying emulsion stability (Turbiscan) based on light backscattering or transmission. Analysis of variance and other statistics were used to analyze the results. Findings: The paper makes an available proxy model that can predict the stability of petroleum emulsions in the presence of wax, calcites and clays. The findings suggest that in the presence of significant amount of wax (0.3 Wt.), the presence of relatively lower concentration of clay (0.1 Wt.) produces very stable petroleum emulsions. The results show that the most stable emulsion is obtained when significant amount of wax exists in the continuous phase and that a concentration of calcites more than wax (in a ratio of at least 2:1) produces an emulsion that separates very fast, indicating low stability. Research limitations/implications: Due to the variations in the amount of asphaltene and resins in crude oils, the proxy model cannot generally predict the stability of every emulsion that forms in the presence of these solids. To have a more general model, it should include asphaltene/resin. This can be tested further. Practical implications: This paper provides useful information to the oil industry, especially where formation of severely stable emulsion is a problem. It also establishes the relationship that exists between solids in emulsion stabilization. Originality/value: This paper satisfies a demand on the effects of other surface-active materials in addition to asphaltene/resin in stabilizing petroleum emulsions. Â© 2019, Emerald Publishing Limited.